Multilayered epithelium at the gastroesophageal junction is a marker of gastroesophageal reflux disease: Data from a prospective Central European multicenter study (histoGERD trial) - Langner, Cord; Wolf, Eva Maria; Plieschnegger, Wolfgang; Geppert, Michael; Wigginghaus, Bernd; Höss, Gabriele M.; Eherer, Andreas; Schneider, Nora I.; Rehak, Peter; Vieth, Michael (Virchows Archiv, 2014)
Multilayered epithelium is defined as hybrid epithelium with characteristics of both squamous and columnar epithelia. Our aim was to evaluate the clinicopathological significance of the lesion by relating its presence to various histological and clinical and/or endoscopic features indicating gastroesophageal reflux disease (GERD). A total of 1,071 individuals participated in a prospective cross-sectional study (576 females and 495 males; median age 53 years). Biopsy material was systematically sampled from the gastroesophageal junction. The histological diagnosis of esophagitis was made according to the Esohisto consensus guidelines. The endoscopic diagnosis of esophagitis was made according to the modified Los Angeles classification and the diagnosis of Barrett's esophagus according to Prague's C & M criteria, respectively. Multilayered epithelium was identified in 103 (9.6 %) individuals, frequently within or adjacent to the ducts of esophageal glands. Its presence was associated with increasing age (p < 0.001), high BMI (p = 0.026), hiatal hernia (p < 0.001), and the endoscopic diagnoses of esophagitis (p = 0.002) and Barrett's esophagus (p < 0.001). Upon histology, multilayered epithelium was associated with features of the squamous epithelium indicating GERD, particularly intercellular space dilation (p = 0.005), and presence of cardiac mucosa (<0.001). For intestinal metaplasia, a trend was noted (p = 0.094). In conclusion, multilayered epithelium was observed in about every tenth individual undergoing upper gastrointestinal endoscopy. The association with histological and clinical features indicating GERD advocates the lesion as a promising new marker for reflux esophagitis. The association with cardiac mucosa and Barrett's esophagus suggests multilayered epithelium to be an intermediate step in the development of columnar metaplasia and, ultimately, Barrett's esophagus. © 2014 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett's esophagus; Gastroesophageal junction; Metaplasia; Multilayered epithelium; Prevalence; Reflux esophagitis